2013
DOI: 10.1074/jbc.m113.501676
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of Mice Null for Liver or Intestinal Fatty Acid-binding Proteins Reveals Highly Divergent Phenotypic Responses to High Fat Feeding

Abstract: Background:Intestinal and liver fatty acid-binding proteins (IFABP and LFABP) are coexpressed in the enterocyte, but their individual functions are not known. Results: High fat feeding promotes different phenotypes in IFABP-and LFABP-null mice. Conclusion: IFABP and LFABP have unique intracellular functions, which in turn produce divergent whole body effects. Significance: Enterocyte FABP ablation modulates intestinal lipid metabolism, which contributes to altered systemic energy homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(85 citation statements)
references
References 82 publications
8
61
0
16
Order By: Relevance
“…This result was reproducible by others using the same line of mice ( 21 ). However, in contrast, FABP1…”
Section: For Example Fabp1supporting
confidence: 56%
See 1 more Smart Citation
“…This result was reproducible by others using the same line of mice ( 21 ). However, in contrast, FABP1…”
Section: For Example Fabp1supporting
confidence: 56%
“…FABP1 can, therefore, affect enzyme function by its effect on ligand availability and targeting ( 21 ), modulate enzyme activity by changing membrane structure and fl uidity ( 22 ), and regulate gene expression through activating nuclear receptors ( 23 ). PPARs and FABP1 are both found in the nucleus and likely interact directly as part of a signal transduction pathway ( 23,24 ).…”
Section: Fabp1 As a Cellular Antioxidantmentioning
confidence: 99%
“…The level of fat chosen, 45 kcal %, is used to promote obesity in mice [13] using physiologically relevant fat levels and without lowering carbohydrate to an extent that could promote ketogenesis [14]. The body weights were measured weekly, daily food intake and whole-body fat mass determined, and euthanasia performed as described [15]. The studies were approved by and conducted in accordance with Rutgers University Institutional Animal Care and Use Committee policies.…”
Section: Animal and Dietsmentioning
confidence: 99%
“…These mice do not show overt fat malabsorption, indicating that either these FABPs play minor roles in fat absorption or their functions in the process can be compensated for when they are absent. Upon high-fat feeding, mice lacking IFABP showed increased energy expenditure and less weight gain, while mice lacking LFABP showed a propensity to gain weight in a recent study ( 44 ). Other studies, however, found male mice lacking IFABP had greater liver mass and gained more weight under high-fat feeding than wild-type control mice did ( 45,46 ), and mice lacking LFABP were protected against obesity and hepatic steatosis induced by diet without malabsorption of dietary fat ( 47 ).…”
Section: Enzymatic Pathways Mediating Intestinal Tag Synthesismentioning
confidence: 92%